(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The posterior parts of the brain are nourished by the vertebral arteries passing in the canal of the transverse processes of the cervical vertebrae. Blood circulation in the vertebrobasilar regionoften can be impaired and the reason for this is mainly the influence of the bone structures of the cervical spine (spondylogenic factor). The consequence of such changes can be caused a slight decrease in cerebral circulation to ischemic complications in the vascular bed (vertebrobasilar insufficiency).